Analgesic efficacy and safety of methylene blue combined with cocktail for periarticular infiltration following total knee arthroplasty: a prospective, randomized, controlled study - Yijiang Deng; Yong Yang; Feng Zhu; Wenzhi Liu; Jiarui Chen; Guangmin Xu (Perioperative Medicine)
Abstract Objective This study aims to explore the analgesic effects and safety of periarticular injections of methylene blue (MB) combined with a cocktail formulation following total knee arthroplasty (TKA). Methods A total of 70 patients undergoing total knee arthroplasty were selected and divided into two groups based on the cocktail formula used for periarticular infiltration, including the methylene blue group (M group, n = 35) and the control group (C group, n = 35). Both groups underwent spinal anesthesia. At the end of the surgery, the M group received a 0.05% methylene blue combined cocktail for periarticular infiltration block, while the C group received a conventional cocktail infiltration block. Postoperatively, both groups used intravenous patient-controlled analgesia. Then, the rest and movement Numeric Rating Scale (NRS) scores, postoperative sufentanil consumption, postoperative inflammatory markers, and the occurrence of adverse reactions such as wound infection and poor wound healing were compared after postoperative 24 h, 48 h, 72 h, and 7-day, 14-day, 28-day between the two groups. Results The rest and during movement, NRS scores at postoperative 24 h, 48 h, 72 h, 7-day, 14-day, and 28-day were significantly lower in the C group compared with the M group (P < 0.05). The total sufentanil consumption at postoperative 72 h was less in the M group (98.9 ± 11.3 µg) compared to the C group (129.1 ± 12.3 µg) (P < 0.01). It also showed a lower IL-6 in the M group at postoperative 24 h and 72 h (P < 0.05). However, there were no significant differences in CRP levels between the two groups at 24 h and 72 h post-surgery (P > 0.05), and neither group experienced complications such as wound infection or poor wound healing. Conclusion Methylene blue combined with a cocktail can be safely used for local infiltration after knee arthroplasty, which reduces postoperative opioid consumption and suppresses the release of inflammatory factors. Moreover, it synergistically enhanced the local anesthetic analgesia and provided sustained pain relief for at least 4 weeks.